1188 Management of Prosthetic Joint Infections and Fracture Related Infections at A District General Hospital. (12th October 2021) - Rajgor, H; Ponniah, G; Li, M; Osman, K; Moores, T
Abstract: Aim: The aim of our study was to determine if there was cohesion in management of orthopaedic infections between the surgical and microbiology team to ensure optimal patient outcome in accordance with BOA standards for management of Orthopaedic infections. Surgical sampling intraoperatively of orthopaedic infections was evaluated. Method: We retrospectively reviewed 19 patients that had suspected PJI or fracture related infections between July 2019 to December 2019 at a District General Hospital. Patient information was collated from patient notes, fusion, bone infection database and MDT notes. Analyses were performed using R (R Foundation for Statistical computing, Vienna, Austria). Results: 19/19 patients had a preoperative antibiotic plan prior to index surgery. 0% of discharge summaries contained information for patients or primary care staff regarding management of a suspected orthopaedic infection. 100% of patients who were septic were reviewed by a consultant within 24hours of admission. 72% of patients that had operative intervention had 5 microbiology + 2 histology samples. 0% of patients had surgical recording of process of sampling. All patients were discussed at the newly formed Bone infection MDT with a microbiology consultant, radiologist, and allied health professionals. Conclusions: For optimal management of orthopaedic infections an MDT approach is vital. Early microbiological input and appropriate surgical sampling and debridement are key to providing a diagnosis of deep infection. The newly created PJI pathway will aid future management of orthopaedic infections and standardise care.